Oxidation Degradation of Rhodamine B in Aqueous by UV/S2O8 2− Treatment System - Xiaoyang Chen; Zhiyong Xue; Yanlai Yao; Weiping Wang; Fengxiang Zhu; Chunlai Hong (International Journal of Photoenergy)
The UV photolysis of persulfate (S2O8 2−) is a novel advanced oxidation technologies (AOTs), which leads to the formation of strong oxidizing radicals, sulfate radicals (SO4 •−). The effect of oxidant S2O8 2− concentration, initial dye concentration, initial pH of solution, and various inorganic anions (Cl−, H2PO4 −, and HCO3 −) were investigated using Rhodamine B (RhB), a kind of xanthene dye, as a model pollutant. With the increase of oxidant S2O8 2−, more SO4 •− produced to attack RhB molecules and result in the increase of RhB degradation. While the improvement was not sustained above a critical value, beyond which degradation rate does not increase. Initial pH of solution had great effect on the RhB degradation rate during UV/S2O8 2− system. SO4 •− is rather stable in acidic solutions, while increasing system pH results in the transformation of SO4 •− to •OH. The effects of three inorganic anions (Cl−, H2PO4 −, and HCO3 −) all had some negative effect on the degradation of RhB. Based on the RhB solution changes of the UV-vis absorption intensity during the UV/S2O8 2− treatment, decolorization of RhB accompanied the destruction of aromatic ring structures of RhB molecules.